2011
DOI: 10.1007/s11832-011-0366-y
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dysplasia of the hip: Impact of sonographic newborn hip screening on the outcome of early treated decentered hip joints—a single center retrospective comparative cohort study based on Graf's method of hip ultrasonography

Abstract: Compared to the era before the institution of a sonographic hip screening programme according to the Graf-method in Austria in 1992, ultrasound screening based-treatment of decentered hip joints has become safer, shorter and simpler: "safer" means lower rate of AVN, "shorter" means less treatment time due to earlier onset and "simpler" means that the devices are now less invasive and highly standardized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 51 publications
(76 reference statements)
3
31
0
2
Order By: Relevance
“…In Norway, it has been estimated that 9% of all primary hip replacements are caused by DDH [19]. Our study’s successful treatment and follow-up strategy is supported by a recent publication by Tschauner et al that concluded that “ultrasound screening based-treatment of decentered hip joints has become safer, shorter and simpler: ‘‘safer’’ means lower rate of avascular necrosis, ‘‘shorter’’ means less treatment time due to earlier onset and ‘‘simpler’’ means that the devices are now less invasive and highly standardized” [20]. …”
Section: Discussionsupporting
confidence: 57%
“…In Norway, it has been estimated that 9% of all primary hip replacements are caused by DDH [19]. Our study’s successful treatment and follow-up strategy is supported by a recent publication by Tschauner et al that concluded that “ultrasound screening based-treatment of decentered hip joints has become safer, shorter and simpler: ‘‘safer’’ means lower rate of avascular necrosis, ‘‘shorter’’ means less treatment time due to earlier onset and ‘‘simpler’’ means that the devices are now less invasive and highly standardized” [20]. …”
Section: Discussionsupporting
confidence: 57%
“…The increase in late DDH cases in Australia and abroad contrasts with the experience of centres that practise universal ultrasound screening of all neonates 1 , 2 . Evidence for the value of universal ultrasound screening includes reduced rates of surgery, hospitalisation, and late diagnoses in screened children 1 , 2 . A variety of ultrasound methods have been successfully employed for screening, and, although variation in interpretation has been reported, this tends to occur with degrees of dysplasia of lesser clinical relevance 23 .…”
Section: Discussionmentioning
confidence: 89%
“…The increase in late DDH cases in Australia and abroad contrasts with the experience of centres that practise universal ultrasound screening of all neonates 1 , 2 . Evidence for the value of universal ultrasound screening includes reduced rates of surgery, hospitalisation, and late diagnoses in screened children 1 , 2 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations